Estimating the economic income and social contributions derived from the South African west coast rock lobster fishery. Issue 3 (3rd July 2022) - Eggers, JM; Cochrane, KL; Sauer, WHH
Abstract : The west coast rock lobster Jasus lalandii fishery is South Africa's third-most-valuable fishery, although the stock is currently estimated at <2% of its pristine biomass. Recent ecologically necessary reductions in the total allowable catch (TAC) had negative economic impacts on stakeholders; however, these have not been quantified as current research into the socio-economic aspects of this fishery is limited. This study explored trends in the net seasonal income and employment opportunities of the fishery in the seasons 2016/17–2018/19 for its different sectors and representative individuals, by analysing records from the government authority and data collected from stakeholders in this fishery through interviews ( n = 30) and surveys ( n = 19). The results indicate that though the fishery was profitable over the three seasons, with the estimated contribution to gross national income ranging from R453 185 000 (US33 302 714) in 2018/19 to R564 721 000 (US41 499 039) in 2017/18, the decreasing quotas had a disproportionate negative effect on some of the representative individuals examined within the different sectors. These worrying economic trends for the different stakeholders indicate that, for effective resource recovery and equitable distribution of fishing opportunities, the socio-economic context of the fishery must be studied more extensively and must be included more directly in management decisions.